Mapping the Trends in Lecture Productivity Research Through Vosviewer-Based Bibliometric Analysis - Juliastuti; Syadeli Hanafi; Aceng Hasani (PT Inovasi Pratama Internasional, 2025)
Objective: This research aims to map the trends in lecturer productivity research through VOSViewer-based bibliometric analysis. Theoretical Framework: This research explains the data analysis on the topic of lecturer productivity and its development using mapping tools on VOSViewer over five years. (2019–2024). Method: This method uses qualitative descriptive analysis to illustrate the performance of bibliometric analysis in forming a network visualization of the chosen theme. Results and Discussion: From the research results over five years (2019–2024), 1000 relevant published journals were found and classified into four clusters according to their publication years. Then, through the classification of journal data, a total of 66 articles published on the theme of lecturer productivity from 2019 to 2024 were identified. From the search results, there are 10 articles with the most or highest citations. It can be concluded that lecturer productivity is a field that can be combined with other fields to be studied. Research Implications: In the era of the Industrial Revolution 4.0, bibliometric analysis is necessary to visually display mapping tools, especially in the education sector. The VOSviewer software application serves as a mapping tool to discover new items or trends, keywords, and the evolution process of the frequency of specific themes in research to obtain various information about scientific developments. Originality/Value: This analysis step is used to facilitate first-time users in accessing and utilizing VOSViewer. This research explains the data analysis on the topic of lecturer productivity and its development using mapping tools on VOSViewer over five years. (2019–2024). Thus, this research is expected to serve as a resource for researchers conducting studies and determining research titles.